As contribuições do Geogebra para a aprendizagem em geometria espacial no 9º ano do ensino fundamental - Silva, Francisco Thiago da (2024)
Given the difficulty that elementary school students have in identifying, classifying and solving problem situations involving basic elements of spatial geometry, this paper analyzes the use of GeoGebra software as a pedagogical resource in the learning of mathematics in a 9th grade class of elementary school, thus generating a reflection on the use of this technology in the teaching-learning process. Analyzing the difficulty that students reveal when faced with problems involving the recognition and identification of vertices, faces and edges of a polyhedron, and solving questions about the volume of solids, the following problem arises: What contributions does GeoGebra software bring to the learning of spatial geometry in the 9th grade of elementary school? Based on this issue, grounded in the socio-interactionist theory regarding mediation and concept formation, the objective of this work is to present the use of GeoGebra software as a pedagogical instrument of mediation and its contributions to the formation of Spatial Geometry concepts in the 9th grade of Elementary School, supported by the methodological assumptions of the Fedathi Sequence. The methodology of this work relies on the qualitative research method, of the exploratory type, taking elements of a participatory research. The research subjects are 9th grade students at Elementary School of a municipal school in Fortaleza. The Didactic Sessions, the field diary and the follow-up questionnaires served as data collection instruments. Based on the data analysis, the use of GeoGebra contributes to the understanding of Spatial Geometry concepts, assists in the faster construction of polyhedra, contributes to the visualization of faces, edges and vertices of polyhedra and facilitates the identification of the faces of a polyhedron. We consider that this work highlights the contributions of the use of GeoGebra, combined with the Fedathi Sequence, based on the socio-interactionist theory for learning the concepts of Spatial Geometry